Improvements and limitation of soy protein‐based adhesive: A review. Issue 10 (25th August 2021) - Lamaming, Sofie Zarina; Lamaming, Junidah; Rawi, Nurul Fazita Mohammad; Hashim, Rokiah; Kassim, Mohamad Haafiz Mohamad; Hussin, Mohd Hazwan; Bustami, Yazmin; Sulaiman, Othman; Amini, Mohd Hazim Mohamad; Hiziroglu, Salim
Abstract: Soy protein is known for its eco‐friendly, sustainable, and biodegradable qualities that are likely used as raw material in producing bioadhesive. However, soy protein‐based adhesive are lacking in terms of adhesive strength and water‐resistance compared to commercial formaldehyde‐based adhesives such as phenol and urea‐formaldehyde resin. Therefore, continuous research has been done to improve adhesive performance. This can be done via physical or modification methods, including the usage of cross‐linking agents, structural modification, enzymatic modification, and the addition of additives. This review will cover these modification methods that give significant enhancement to the water‐resistance and adhesive strength of soy protein‐based adhesives. Abstract :